EXPERIMENTAL COMPARATIVE STUDY OF ADSORPTION ISOTHERMS AND KINETIC PARAMETERS OF NATURAL SURFACTANTS ON NANOSTRUCTURED SORBENTS (Universal International Scientific Journal, 2026)
In this article, the adsorption processes of natural surfactants (SFM) on the surface of nanostructured sorbents were experimentally studied in a comparative manner. The adsorption isotherms and kinetic parameters of biosurfactants obtained from plant sources on nanocomposite sorbents based on nanosilica, carbon nanomaterials and metal oxides with different structures were studied. The adsorption equilibrium was analyzed using Langmuir and Freundlich isotherms, and the kinetic properties were estimated based on pseudo-first and pseudo-second order kinetic models. As a result of the experiments, the high adsorption capacity, rapid equilibrium achievement and the superiority of the chemisorption mechanism of nanostructured sorbents were determined. The obtained results serve as a scientific basis for the creation of environmentally friendly and effective sorbents
Keywords: nanostructured sorbents; natural surfactant; biosurfactant